Agricultural Dynamics and Economic Growth: Evidence from Devel oped and Developing Indian States - Sinha, Jitendra Kumar (New Countryside, 2026)
This study investigates the role of agricultural productivity, technological intensification, and structural factors in shaping economic growth across developed and developing Indian states. Using a balanced panel dataset of 22 states over the period 2001–2024 (528 observations), the analysis employs correlation techniques, fixed-effects estimation, sub-sample analysis, and Feasible Generalized Least Squares (FGLS) to test a set of theoretically grounded hypotheses on the agriculture–growth nexus. The findings reveal pronounced structural heterogeneity across state groups. Agricultural productivity, proxied by gross value added per worker, emerges as a robust and statistically significant driver of economic growth across both developed and developing states, with relatively stronger transmission effects in more advanced economies. Technological inputs exhibit stage-specific impacts: mechanization significantly enhances growth in developing states, whereas fertilizer intensity plays a more prominent role in developed states. The interaction between machinery and fertilizer is positive and significant, confirming the complementarity hypothesis and indicating that integrated technological adoption yields higher productivity gains than isolated inputs.Agricultural trade openness exerts a consistently positive and significant effect, particularly in developed states, supporting the openness-led growth hypothesis, while its impact in developing states remains contingent on structural competitiveness. Human capital and research and development (R&D) show weak or negative short-run effects, reflecting adjustment costs and lagged returns to innovation. Population growth contributes positively, whereas institutional quality exhibits mixed but robust effects across specifications. Overall, the results highlight the importance of context-specific policy frameworks that integrate productivity enhancement, technological complementarities, trade integration, and institutional capacity for achieving sustainable and inclusive economic growth.